A Case Report of Wernicke's Encephalopathy Associated With Schizophrenia - He, Jingqi; Li, Jinguang; Li, Zhijun; Ren, Honghong; Chen, Xiaogang; Tang, Jinsong (Frontiers in Psychiatry, 2021)
Introduction: Wernicke's encephalopathy (WE) is a severe neurological syndrome often associated with alcoholism. Clinicians tend to ignore WE in other nonalcoholic clinical settings related to malnutrition and thiamine deficiency, resulting in delayed diagnosis. The diagnosis becomes more difficult when WE are secondary to psychiatric illnesses, as symptoms can be masked by the primary disease. Case presentation: We present a case of a 56-year-old female patient with schizophrenia who was admitted to the hospital for mental and behavior disorder, without history of alcohol. She presented symptoms of ophthalmoplegia and high muscular tension, and the brain MRI showed symmetric lesions in bilateral basal ganglia and third ventricle. She responded well to thiamine and was discharged on hospital day 22. Conclusion: The psychiatrists should be on the alert for starvation-induced WE, especially for the patients suffering from malnutrition. WE is a preventable and treatable disease, so once suspected WE, patients ought to take adequate supplements of thiamine immediately.